Anthropomorphology of the sartorial muscle (m. sartorius) in ontogenesis of man - Kołaczkowski, Zdzisław; Jakubowicz, Marian; Marecki, Bogusław; Wawrzyniak , Stanisław (Anthropological Review, 1974)
Research work has been carried out on 17 fetuses of both sexes their Si ranging from 41 - 175 mm (9 - 20 week) and on 30 extremities of adult subjects. The sartorial muscle was studied by describing it and a number of measurements was taken, afterwards indices were calculated: to make a comparision of fetuses who have Si ranging from 41-175 mm (9 - 20 week) with fetuses studied by Kołaczkowski and Burchardt [6] whose Si were from 195-320 mm (21-39 week) and with adult subjects. It was found in fetuses having Si from 41 - 175 mm that their farthest point from which the fleshy part of muscle descends more frequently lies above the fissure of the knee joint (29.5%) than in fetuses with Si ranging from 195 - 320 mm — (2.0%). In adult subjects on the other hand the fleshy part of the muscle is being transformed into its tendon above the fissure of the knee joint in as much as 46.7%. While the fetuses grow older their relative length of the fleshy part of the sartorial muscle also increases. In the period beyond the fetal stage this length is shorter with male subjects whereas in female subjects it is greater than in fetuses whose Si ranges from 195 - 320 mm (21 - 39 week). The farthest point of descending of muscular fibres as well as the farthest point.of terminal attachement of the sartorial muscle decreases while the fetuses grow older whereas in the period bey- ond the fetal stage the relative length of the fleshy part as well as the length of the tendon of the muscle become shorter.